The Impact of COVID-19 on Parental Perception of Oral Health-Related Quality of Life of Children: A Comparison of a Sample from Saudi Arabia and Kuwait - Wasmiya A. AlHayyan; Abdulrahman D. AlSaffan; Maram I. Alenezi; Bashaer K. Almutairi; Lena F. Alammari; Sharat Chandra Pani (Hindawi Limited, 2023)
Background and Aim. The COVID-19 pandemic has impacted access to dental care for children over the world. This study aimed to assess the impact of the COVID-19 pandemic on parentally reported oral health-related quality of life (OHRQoL) in Riyadh, Saudi Arabia and Kuwait City, Kuwait. Materials and Methods. OHRQoL was measured using a a validated Arabic version of the Child Oral Health Impact Profile (COHIP). Parents of children aged between 5 and 9 years were administered questionnaire during the COVID-19 pandemic. The responses were compared across the different domains of the questionnaire between the two countries using the Mann-Whitney U test. Differences were also tested between the parents of males and females separately in each city. The correlation of the COHIP scores with the age of the child was done using the Spearman's rho. Results. No significant differences in overall COHIP scores were found between the parents in Riyadh and Kuwait City (p>0.05). There were significant gender differences observed across domains in Kuwait (p=0.030) but not in Riyadh (p=0.295). There was also a significant negative correlation between the different COHIP domains in Kuwait but not Riyadh. Conclusion. There is a greater gender difference and age correlation of OHRQoL among the population studied in Kuwait City when compared to those in Riyadh.